Surgical Approaches for Minimally Invasive Interlocking Nail Osteosynthesis in Dogs - de Lucena, Dayvid Vianêis Farias; Minto, Bruno Watanabe; Neto, José Aloizio Gonçalves; Ferreira, Danyelle Rayssa Cintra; Dias, Luís Gustavo Gosuen Gonçalves (VCOT Open, 2023)
Objective The aim of this article was to describe, in detail, the safe portals and surgical approaches for minimally invasive interlocking nail osteosynthesis.Methods Fifteen dog cadavers weighing between 30 and 40 kg were used, 10 for an anatomical study and 5 for creation of the minimally invasive interlocking nail osteosynthesis portals. Anatomical dissections were used to establish landmarks and precise anatomical interrelationships of the surgical approaches for the minimally invasive use of interlocking nails in the tibia, femur, and humerus. Subsequent dissection was made to evaluate potential iatrogenic lesions.Results The reference points for, and anatomical interrelationships of, the minimally invasive surgical approaches to the tibial, femur, and humerus diaphyses were detailed. No damage to any important neurovascular structures was observed in any cadaver.Conclusion Safe portals for approaching the humerus, femur, and tibia were described in detail to allow safe application of interlocking nails in a minimally invasive fashion.
Keywords: biological osteosynthesis; canine; fracture; safe corridors